2000
DOI: 10.1002/1096-8644(200011)113:3<389::aid-ajpa9>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density, osteopenia, and osteoporosis in the rhesus macaques of Cayo Santiago

Abstract: This cross-sectional study investigates metabolic bone disease and the relationship between age and bone mineral density (BMD) in males and females of a large, well-documented skeletal population of free-ranging rhesus monkeys (Macaca mulatta), from the Caribbean Primate Research Center Museum collection from Cayo Santiago, Puerto Rico. The sample consists of 254 individuals aged 1.0-20+ years. The data consist of measurements of bone mineral content and bone mineral density, obtained from dual-energy X-ray ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 45 publications
2
61
0
Order By: Relevance
“…As in women, bone development accelerates peripubertally in these monkeys, with final closure of the epiphyses and attainment of peak bone mass in both rhesus and cynomolgus monkeys occurring by about 10 yr of age (Cerroni et al 2000;Hotchkiss et al 2001). At this point in development, the monkeys are probably equivalent to 30-yr-old women.…”
Section: Use Of Nonhuman Primates To Model the Etiology And Sequelae mentioning
confidence: 94%
“…As in women, bone development accelerates peripubertally in these monkeys, with final closure of the epiphyses and attainment of peak bone mass in both rhesus and cynomolgus monkeys occurring by about 10 yr of age (Cerroni et al 2000;Hotchkiss et al 2001). At this point in development, the monkeys are probably equivalent to 30-yr-old women.…”
Section: Use Of Nonhuman Primates To Model the Etiology And Sequelae mentioning
confidence: 94%
“…The second study [58] utilized 58 female rhesus monkeys aged 4-30 yr and reported reduced bone mass in older postmenopausal monkeys at the total body, spine, and distal radius sites. Another study [59] reported slight but significant reductions in lumbar vertebrae BMD from 131 female rhesus skeletons aged 17-22 yr. Finally, a study in 20 premenopausal rhesus monkeys aged 8-23 yr [60] reported a significant age-associated bone loss at two radial sites, estimated at less than 5% per year in monkeys that reached peak bone mass, but not for total body or spine bone mass.…”
Section: Bone Changes Caused By Aging and Menopausementioning
confidence: 99%
“…Many clinical studies of bulk BMD (or apparent density) continue to use PD technology in assessing bone mineral mass (i.e., mineral content) or mineral areal density g/cm 2 (e.g. [5,8,13,29,30,39]). While technologies more advanced than clinical CT or PD exist, many of these (e.g., pQCT and µCT) are currently less accessible than clinical CT, much less PD, due largely to even greater financial and time constraints of acquiring bulk BMD data from hundreds of ROIs.…”
Section: Introductionmentioning
confidence: 99%